The THE EFFECT OF DONEPEZIL ON THE IMPROVEMENT OF COGNITIVE FUNCTION AND PLASMA BRAIN-DERIVED NEUROTROPHIC FACTOR (BDNF) LEVELS IN SCHIZOPHRENIA - Lisal T Sonny; Lompi Fadillah Aulya; Hawaidah; Bahar Burhanuddin; Limoa Erlyn; Tammasse Jumraini; Syamsuddin Saidah (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Abstract Background : Donepezil administration as adjuvant therapy in schizophrenic patients is considered to improve cognitive function and is associated with increased levels of BDNF which has been widely studied as a cognitive marker for schizophrenia. The purpose of this study was to determine the effect of Donepezil on the improvement of cognitive function and plasma BDNF levels in patients with schizophrenia. Objective : To determine the effect of adjuvant therapy of donepezil in improving cognitive function and BDNF levels in schizophrenic patients receiving risperidone. Method : Forty-four (44) schizophrenia inpatient were divided into two groups, the research group, and the control group. Both groups received Risperidone 4 mg/day, and only the treatment group was received 5 mg donepezil for 6 weeks. To assess cognitive function, the SCoRS v BI scale was used and plasma BDNF levels were measured. Independen t tests, Wilcoxon, Friedman and Spearman correlation tests were performed to assess the difference means between groups. Results : There was a significant improvement in cognitive function in both groups (p<0.05). Although there was an increase in plasma BDNF levels in both groups, only research group was statistically significant at (p<0.05). The comparison of changes in the SCoRS v BI scores, plasma BDNF levels and in the correlation in both group was significant (p <0.05). Conclusion The addition of adjuvant therapy donepezil to standard therapy Risperidone 4 mg/day was associated with improved cognitive function and also associated with increased plasma BDNF levels.